Evaluation Instruments for Quality of Life Related to Melasma: An Integrative Review - Pollo, Camila Fernandes (Clinics (Sao Paulo), 2018)
The aim of this study was to analyze scientific production concerning the validation and cultural adaptation of quality of life evaluation instruments for patients with melasma and to offer a critical reflection on these methods. A literature review was performed based on a search of the Web of Science, Bireme, PubMed, Elsevier Scopus, and Google Scholar databases. All published articles from indexed periodicals in these electronic databases up to December 2015 were included. Eight articles were identified, of which only one (12.5%) referred to the development and validation of a specific instrument for evaluation of the quality of life of melasma patients. An additional six articles (75%) referred to transcultural adjustment and validation of the same instrument in other languages, and another (12.5%) article reported the development of a generic instrument for evaluation of quality of life in patients with pigment disorders. This review revealed only one specific instrument developed and validated in different cultures. Despite being widely used, this instrument did not follow the classic construction steps for psychometric instruments, which paves the way for future studies to develop novel instruments.